Mechanical Mixing and Deaeration Station for Adhesive Compositions - Miturska-Barańska, Izabela (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2023)
This paper presents the design of a specialised mixing and deaeration station for adhesive compositions. The aim of the work was to present a device for simultaneous mixing and gas bubble removal, as well as to verify the correctness of the practical application of the station by conducting experimental tests. In the experimental research, the subject of the study was an adhesive composition of the Epidian 5 epoxy resin with the PAC curing agent, which was prepared using four mixing methods carried out with the use of the station for simultaneous mixing and deaeration. In addition, the composition was physically modified by adding particles of CaCO3 calcium carbonate to verify the correct mixing of the composition components. The prepared samples were subjected to tensile and compression strength tests. The structure of the prepared samples was also analysed using scanning electron microscopy (SEM). The tests carried out showed that the stand for simultaneous mixing and deaeration of adhesive compositions meets the expectations set for it. Mixing variant 4, in which mixing was realised using a dispersing disc mixer, proved to be the most favourable mixing method. Mixing was carried out at a speed of 1170 rpm for 3 minutes. In addition, during the mixing process, a deaeration process of the mixed composition was carried out, as well as deaeration was realised after the mixing process in a time of 2 minutes. Changing the mixing parameters contributed to an increase in both the tensile strength and compression strength of the tested compositions. SEM analysis of the observed samples showed that changing the mixing parameters reduced the amount of air bubbles in the adhesive structure and, in the case of modified compositions, resulted in a better distribution of the filler in the structure of the mixed compositions.